2003
DOI: 10.1101/gad.267103
|View full text |Cite
|
Sign up to set email alerts
|

Canonical Wnt signals are essential for homeostasis of the intestinal epithelium

Abstract: To assess the critical role of Wnt signals in intestinal crypts, we generated transgenic mice ectopically expressing Dickkopf1 (Dkk1), a secreted Wnt inhibitor. We find that epithelial proliferation is greatly reduced coincidentally with the loss of crypts. Although enterocyte differentiation appears unaffected, secretory cell lineages are largely absent. Disrupted intestinal homeostasis is reflected by an absence of nuclear ␤-catenin, inhibition of c-myc expression, and subsequent up-regulation of p21. Thus, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
729
4
4

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 915 publications
(765 citation statements)
references
References 28 publications
28
729
4
4
Order By: Relevance
“…Wnt signaling plays an important role in the maintenance of the intestinal crypt containing the stem cells and undifferentiated progenitor cells 14,15 . In the gastric gland, Wnt signaling also keeps the progenitor cells undifferentiated in the isthmus of the gastric gland, as we have shown that the number of progenitors increased significantly in the K19-Wnt1 mouse stomach.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wnt signaling plays an important role in the maintenance of the intestinal crypt containing the stem cells and undifferentiated progenitor cells 14,15 . In the gastric gland, Wnt signaling also keeps the progenitor cells undifferentiated in the isthmus of the gastric gland, as we have shown that the number of progenitors increased significantly in the K19-Wnt1 mouse stomach.…”
Section: Discussionmentioning
confidence: 99%
“…Given that Wnt signaling is essential for maintaining the intestinal crypt that contains epithelial progenitor cells and stem cells 14,15 , we examined gastric epithelial differentiation in the K19-Wnt1 mice. The trefoil factor 2 (TFF2) was used as an undifferentiated epithelial marker, because it was detected in the small isthmal cells ( Figure 3A and B) where β-catenin accumulated in both the nucleus and cytoplasm ( Figure 3C).…”
Section: Suppression Of Gastric Epithelial Differentiation By Wnt Actmentioning
confidence: 99%
“…In the colon, loss of TCF4 or Dkk over-expression promotes loss of stem cells in the colon crypt, indicating that Wnt signaling is required for maintenance of the stem cell compartment [40][41][42]. Wnt signaling may therefore be a fundamental regulator of stem cell choices to proliferate or self-renew.…”
Section: Wnt Signaling In Cancer and Human Diseasementioning
confidence: 99%
“…Wnt/␤-catenin signaling has been implicated in a variety of physiological and pathological processes, including epithelial-mesenchymal transition (EMT), cell fate specification, embryonic induction, stem cell homeostasis, and tumorigenesis (Korinek et al, 1997;Maretto et al, 2003;Pinto et al, 2003;Sato et al, 2004;Willert and Jones, 2006). Canonical Wnt signaling leads to cytoplasmic accumulation of hypophosphorylated ␤-catenin, which in turn translocates into the nucleus, interacts with T-cell factor (TCF)/lymphoid enhancer factor (LEF), and regulates expression of diverse Wnt target genes (Korinek et al, 1997;Schmidt and Patel, 2005).…”
Section: Introductionmentioning
confidence: 99%